A new formulation of fluticasone propionate/salmeterol in a metered-dose inhaler (MDI HFA) allows for the reduction of a daily dose of corticosteroid and provides optimal asthma control - A randomized, multi-center, non-inferiority, phase IV clinical study. (January 2021) - Kupczyk, Maciej; Majak, Paweł; Kuna, Piotr; Asankowicz-Bargiel, Beata; Barańska, Eliza; Dobek, Rafał; Garbicz, Sławomir; Jerzyńska, Joanna; Latos, Anna; Machowiak, Wojciech; Majorek-Olechowska, Bernadetta; Olech-Cudzik, Anna; et al.
Abstract: Background: Improvement of the delivery method of inhaled corticosteroids and subsequent dose reduction can minimize the risk of unfavorable outcomes while providing optimal asthma control. Objective: This randomized, multi-center, non-inferiority, phase IV clinical study compared the efficacy and safety of a new formulation of fluticasone propionate/salmeterol (250 μg/50 μg, twice daily) administered in a metered-dose inhaler hydrofluoroalkane (MDI HFA) with a dry-powder inhaler (DPI) containing fluticasone propionate/salmeterol (500 μg/50 μg, twice daily). Methods: Adults with asthma ( n = 231 ) were randomly assigned to either the study group (treated for 12 weeks with fluticasone propionate/salmeterol MDI HFA) or a control group (treated for 12 weeks with fluticasone propionate/salmeterol DPI). Asthma symptoms, exacerbations, short-acting β2 -agonist (SABA) use, physical activity, lung function, and general health status were assessed during four study visits. Results: Compared with the reference drug, the study drug decreased the incidence of daytime and night-time asthma symptoms, asthma exacerbations, self-administration of SABA, and the limitation of physical activity. Comparable improvement in peak expiratory flow ([MDI HFA] from 6.2 ± 0.2 to 6.6 ± 0.2 l/s vs. [DPI] from 6.0 ± 0.2 to 6.9 ± 0.2 l/s; p > 0.05), forced expiratory volume in one second, and forced vital capacity were obtained in both groups. Significantly lower incidence of hoarseness was observed in the study group ([MDI HFA] 0.0% vs. [DPI] 2.8%; p = 0.0267); no major differences were found for other adverse events. Conclusions: Fluticasone propionate/salmeterol (250 μg/50 μg, twice daily) MDI HFA provides optimal asthma control and is non-inferior to fluticasone propionate/salmeterol (500 μg/50 μg, twice daily) DPI. Graphical abstract: Image 1 Highlights: The risk of inhaled corticosteroids side effects is dose- and inhaler-dependent. MDI HFA allows to reduce by half the required dose of fluticasone compared to DPI. Fluticasone propionate/salmeterol MDI HFA provides optimal asthma control. MDI HFA decreased the incidence of hoarseness compared to DPI.